Metode Analisis Keuangan Untuk Pengoperasian Aplikasi Buku Warung - Anike Putri; Ghea Nofayza; Widi Dwi Aditia Putra; Delia Arofah (LPPM Universitas Informatika dan Bisnis Indonesia, 2023)
For MSMEs, several steps can be taken in order to manage finances well, namely starting to separate personal and business finances, and starting simple bookkeeping. If MSMEs are able to separate personal finance from business finance, and have bookkeeping or administrative management (business finance), MSMEs can try to make financial planning in a simple way. By separating personal and business financial records, owners can more easily manage their business finances. This is because the accuracy of business financial records can influence decision making and evaluate business performance. Mixed cash flow between personal and business finances can make it difficult for MSME actors to determine business operating costs. One strategy for separating personal and business financial records is that the owner can